Ekonomska učinkovitost notranjega trga EU - Hojnik, Janja (LeXonomica, 2021)
EU internal market and its economic efficiency. Process of regional economic integration in Europe has in the last decades been determined by expansions in various dimensions – substantially as well as geographically. Market integration is thereby presented as an instrument to enhance prosperity. The article analyses economic effect of the EU internal market, i. e. whether and to what extend has the internal market enhanced economic prosperity and income in Europe in the last half-century. From methodological point of view we are dealing with a very complex question, which has been approached in various ways by various economic studies. The article is based on a study performed by a Dutch bureau CPB, which was assessing additional economic effect of the EU internal market – i.e. in addition to alternative forms of market integration, existing also in economic relations with third countries. The authoress concludes that the EU internal market has achieved the highest economic effect in the field of foreign direct investments; economic effect of free movement of goods is comparable to foreign direct investments, whereas the economic effect of free movement of services is being more moderate, however, having considerable potential for increase. Economic effect of free movement of workers is not analysed in the article considering low level of migration flows between the EU member states. Povzetek. Proces regionalne ekonomske integracije v Evropi je v zadnjih desetletjih zaznamovalo širjenje v različne dimenzije, tako vsebinsko kot geografsko. Pri tem je tržna integracija EU predstavljena kot sredstvo za povečanje blaginje. Prispevek presoja ekonomski učinek notranjega trga EU - tj. povrh alternativnih oblik tržne integracije, ki obstajajo tudi v gospodarskih odnosih s tretjimi državami. Avtorica v prispevku ugotavlja, da je notranji trg EU dosegel najvišji ekonomski učinek pri tujih neposrednih naložbah; ekonomski učinek prostega pretoka blaga je primerljiv s tujimi neposrednimi naložbami, medtem ko je ekonomski učinek pretoka storitev nižji, vendar ima znatni potencial za povečanje. Ekonomski učinek svobode gibanja delavcev zaradi majhnega obsega migracijskih tokov med državami članicami EU v prispevku ni obravnavan.